Investigation of Relationship among Serum Malondialdehyde, Paraoxonase and Liver Function Tests in Acute Poisoning Patients - Alagöz, Gürkan; Durukan, Polat; Yıldız, Mustafa; Bayar, Mustafa Kemal; İlhan, Necip; Çevik, Yunsur; Seçkin, Dilara (Fırat University, 2007)
Objectives: Aim of this study is to determine serum levels of paraoxonase (PON), malondialdehyde (MDA), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma glutamil transferase (GGT) at 6th and 24th hour after the intake of poisonous substances and to investigate the role of these parameters in the follow up and treatment of the patients and the correlation between them. Material and Methods: The study was performed in the emergency department of Firat University Faculty of Medicine between the dates of December 2003 and June 2004 with 82 poisoning patients older than 16 years and matching inclusion criteria prospectively. Results: Eighty-two patients were included to the study. Mean MDA1 and MDA2 levels of these patients were 0.39±0.2 and 0.45±0.3 mmol/mL respectively. Mean PON1-1 and PON1-2 levels were 153.33±77.3 and 146.25±70.7 U/mL respectively. Mean AST1, AST2, ALT1, ALT2, GGT1 and GGT2 levels were 21.53±8.1, 26.73±47.7, 20.16±9.6, 20.87±21.6, 20.75±15.3 and 20.77±20.0 U/L respectively. No statistically significant difference was found among the patients taking tricyclic antidepressants, acetaminophen, mushroom, alcohol, and organophosphates according to serum levels of MDA, PON1, AST, ALT and GGT. Conclusion: We think that the values of MDA, PON1, AST, ALT and GGT at 6th and 24th hour have no role in first 24 hour follow up and treatment of acute poisoning patients. New laboratory parameters may be investigated for the follow up and treatment of poisonings, which are important health problems. ©2007, Firat University, Medical Faculty

Giriş: Bu çalışmanın amacı akut zehirlenme hastalarında, serum paraoksonaz (PON), malondialdehid (MDA), aspartat aminotransferaz (AST), alanin aminotransferaz (ALT), gama-glutamil transaferaz (GGT) değerlerinin, hastaların zehirlenme maddelerini alımından sonraki 6. ve 24. saatlerdeki düzeylerinin belirlenerek, hastaların takibi ve bu değerlerin hastaların tedavisindeki rollerini, aralarında korelasyon olup olmadığını araştırmaktır. Gereç ve Yöntem: Çalışma Fırat Üniversitesi Tıp Fakültesi Acil Servise Aralık 2003 - Haziran 2004 tarihleri arasında zehirlenme nedeniyle başvuran, çalışmaya dahil edilme kriterlerine uyan 16 yaş ve üzeri 82 hasta ile prospektif olarak gerçekleştirildi. Bulgular: Çalışmaya 82 hasta alınmıştır. Bu hastaların MDA1 ve MDA2 değerleri sırasıyla ortalama 0.39±0.2 ve 0.45±0.3 mmol/mL olarak bulunmuştur. PON1-1 ve PON1-2 değerleri sırasıyla ortalama 153.33±77.3 ve 146.25±70.7 U/mL olarak bulunmuştur. AST1, AST2, ALT1, ALT2, GGT1 ve GGT2 değerleri sırasıyla ortalama olarak 21.53±8.1, 26.73±47.7, 20.16±9.6, 20.87±21.6, 20.75±15.3 ve 20.77±20.0 U/L bulunmuştur. Yapılan istatistiksel analiz sonucunda trisiklik antidepresan, asetaminofen, mantar, alkol ve organofosfat zehirlenmesi ile başvuran hastalarda MDA, PON1, AST, ALT ve GGT değerleri arasında istatistiksel olarak anlamlı bir fark bulunmamıştır (p>0.05). Sonuç: Akut zehirlenme hastalarında 6. ve 24. saatlerde alınan MDA, PON1, AST, ALT, GGT değerlerinin ilk 24 saatteki hasta takibi ve tedavisinde yeri olmadığını düşünmekteyiz. Zehirlenme gibi önemli bir sorunun takip ve tedavisinde yeni laboratuvar parametrelerinin araştırılması gerektiğini düşünmekteyiz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Akut Zehirlenme Hastalarında Serum Malondialdehid, Paraoksonaz ve Karaciğer Fonksiyon Testleri Arasındaki İlişkinin Araştırılması